2009
DOI: 10.1183/09031936.00159708
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mortality associated with formoterol: a systematic review and meta-analysis

Abstract: There is concern long-acting b-agonist (LABA) drugs may increase the risk of asthma mortality.We undertook a systematic review which included the AstraZeneca Formoterol Clinical Trial Safety Database and Novartis Food and Drug Aministration Formoterol Briefing Document. Randomised controlled clinical trials of duration o4 weeks that compared formoterol with a non-LABA comparator treatment in asthma were included in a meta-analysis of the risk of all-cause mortality and asthma death. Simple contingency tables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…3,[9][10][11]14 These findings are of clinical relevance because monotherapy with LABAs in patients with poorly controlled asthma may be associated with an increased risk of mortality. [29][30][31][32] This finding would provide support for the recommendation that LABAs are prescribed only as ICS/LABA combination therapy, thereby ensuring that LABA monotherapy cannot occur. 33 Another observation from our study is that subjects were essentially taking their ICS therapy within the framework of variable dosing.…”
Section: Discussionmentioning
confidence: 66%
“…3,[9][10][11]14 These findings are of clinical relevance because monotherapy with LABAs in patients with poorly controlled asthma may be associated with an increased risk of mortality. [29][30][31][32] This finding would provide support for the recommendation that LABAs are prescribed only as ICS/LABA combination therapy, thereby ensuring that LABA monotherapy cannot occur. 33 Another observation from our study is that subjects were essentially taking their ICS therapy within the framework of variable dosing.…”
Section: Discussionmentioning
confidence: 66%
“…4,24 However, there are concerns about the potential for increased asthmarelated mortality associated with the use of long-acting b-agonists, both as monotherapy and in conjunction with ICSs. 4,25,26 In this analysis 80.8% of patients receiving an increased dose of ICS as step-up therapy achieved asthma control, an increase from 66.6% at baseline; the rate of asthma exacerbations decreased, and only 12% to 19% of patients required a subsequent change to combination therapy or additional therapy, most commonly the addition of a long-acting b-agonist.…”
Section: Discussionmentioning
confidence: 97%
“…Several other meta-analyses have been performed to assess the safety of formoterol with or without concomitant ICS in adults and children (12)(13)(14) and the lower risk of asthma-related SAEs reported in the Cates review concur with the Jaeschke (12) and Sears meta-analyses (13). Jaeschke et al reviewed 18 trials in adolescents and adults, and found no evidence of harm associated with the use of formoterol in combination with ICS compared to ICS alone at the same or higher dose (12).…”
mentioning
confidence: 51%
“…However despite the largeincluded population (n = 68, 004 adults and children), there was insufficient power to confirm any association between formoterol use and asthma mortality (13). In the Wijesinghe review and metanalysis, asthma mortality was the only outcome assessed and was, as in previous reviews, inconclusive because of insufficient power to assess this outcome by LABA exposure (14).Despite the increasing number of studies, reviews and meta-analyses, little has changed regarding the controversy surrounding the risk: benefit ratio of LABAs. The findings from the recent Cates review (1) are not entirely reassuring, as analyses were…”
mentioning
confidence: 94%